Modeling and frequency control of community micro-grids under stochastic solar and wind sources - Dhananjay Kumar (Engineering Science and Technology, an International Journal, 2020)
The Community Micro-Grid (CMG) is a coordinated local grid area served by one or more distribution substations supported by local renewable and other distributed energy resources (DER). In an islanded mode, the CMG stability reduces due to low inertia of the equivalent system and stochastic nature of renewable energy sources (RESs). To study the frequency stability of the islanded CMG system, this paper explores the mathematical modeling aspects of different sources in the CMG and the robust control design for the community microgrid model. The robust design using a fixed structure H∞ synthesis method has been presented to compensate for the effect of modeling uncertainty. The uncertainty in the CMG model results in parametric perturbation which degrades its performance and stability. This paper explores the existing mathematical models of CMG’s and different control techniques applied for frequency regulation. Robust controller design for CMG is proposed that can handle the stochastic input disturbances like a sudden change in power coming from solar and wind sources and also the model uncertainty that results in the parametric perturbations. The complete model is simulated using MATLAB Simulink platform and results of frequency deviation obtained by robust and PID controller are compared. The controller hardware in loop (C-HIL) validation of the robust control method for CMG has been done using a real-time controller board (DS1104). This CHIL system also implements the CMG plant-controller model and analyzes the frequency deviation against load and renewable power fluctuations. The oscillations in frequency deviation are analyzed for sudden rise or fall in the renewable power coming from the solar and wind sources. A reduction of 30% is achieved in frequency overshoot and settling time using a robust controller than the PID controller. The controller developed and implemented using H∞ synthesis has robust stability and performance for the perturbed CMG model and also shows a better time response, unlike the PID controller.